2016
DOI: 10.2135/cropsci2016.03.0197
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen Years of Nitrogen Leaching from a Kentucky Bluegrass Turf

Abstract: Most research on nitrate‐nitrogen (NO3–N) leaching in turfgrass was conducted on recently established sites and indicates that leaching poses little risk to the environment. The potential for greater NO3–N leaching from mature turf sites is relatively unknown. Nitrogen (N) leaching from a Kentucky bluegrass (Poa pratensis L.) turf was measured for 15 yr using monolith lysimeters. From 1998 through 2002, half of the lysimeters were treated annually with urea at a high rate of 245 kg N ha−1 (49 kg N ha−1 applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In a 15‐yr field study, Frank et al. (2016) concluded that as a turfgrass system ages there is a critical N application rate above which greater NO 3 –N occurs and below that rate the risk is minimal. At TB, the critical N application rate may have been exceeded but not at SB.…”
Section: Resultsmentioning
confidence: 99%
“…In a 15‐yr field study, Frank et al. (2016) concluded that as a turfgrass system ages there is a critical N application rate above which greater NO 3 –N occurs and below that rate the risk is minimal. At TB, the critical N application rate may have been exceeded but not at SB.…”
Section: Resultsmentioning
confidence: 99%
“…Frank et al. (2016) observed the N saturation phenomenon in a long‐term lysimeter experiment in Michigan, where N leaching rates were low for the first several years, but after consistent N fertilization at high rates, N leaching increased to concerning levels. The leaching losses were not associated with large drainage events.…”
Section: Management Practicesmentioning
confidence: 99%
“…In addition to plant uptake of late‐fall N applications, there are concerns regarding N loss from leaching. Several researchers have reported high N leaching from late‐fall N applications (Frank et al, 2016; Mangiafico and Guillard, 2006; Petrovic et al, 1986). Soldat et al (2017) measured the effect of temperature and evapotranspiration (ET) independently on nitrate N leaching and found increased risk for nitrate N leaching from soluble N applications at temperatures below 50°F.…”
Section: To Convert Column 1 To Column 2 Multiply By Column 1 Suggest...mentioning
confidence: 99%